2018
DOI: 10.15171/jrip.2018.51
|View full text |Cite
|
Sign up to set email alerts
|

Potential adverse effects of amphetamines on kidney; a narrative review on current knowledge

Abstract: Isolated reports on renal complications, rhabdomyolysis, necrotizing renal maculopathy and malign hypertension, induced by amphetamine (AMP) and its analogues have been recorded. This review tried to survey different sources to collect information for better understanding the pathophysiology underlying the functional defects and different renal complications in patients with AMP abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Microvascular obstruction secondary to disseminated intravascular coagulation, myoglobinuria and systemic hypotension lead to AKI. [95] 2.4.3. Clinical characteristics.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Microvascular obstruction secondary to disseminated intravascular coagulation, myoglobinuria and systemic hypotension lead to AKI. [95] 2.4.3. Clinical characteristics.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Studies have shown that the use of NSAIDs has been associated with increased cardiovascular problems and gastrointestinal disorders and also with aggravation of diabetes or renal function. These drugs also inhibit the synthesis of cartilage matrix in humans, which in turn increases the damage of joint cartilage in osteoarthritis [19-22].…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning that individuals with ADHD are more prone to engaging in risky behaviors that may contribute to kidney damage in adulthood, such as substance abuse and poor lifestyle choices (6,7).…”
mentioning
confidence: 99%